The language that unites us is the one that also separates us: Portuguese language use by Brazilian and African youth in Portugal - Iorio, J.; Gaspar, S. (Journal of Language Discrimination, 2024)
This paper analyses whether the Portuguese language spoken by young people from the Community of Portuguese-speaking Countries in Portugal involves dimensions of social inclusion or exclusion. It employs an interdisciplinary approach (with concepts from sociology and linguistics), and a qualitative methodology in the shape of thirty-three interviews with young people from Brazil and Portuguese-speaking countries in Africa living in the Portuguese municipality of Sintra. While ‘speaking Portuguese’ facilitates the integration of these young people, their inclusion is also hindered by the coexistence of this language with other native languages in the case of Africans, and by the use of standard Brazilian Portuguese in the case of Brazilians.